2019
DOI: 10.1177/0972150919846964
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brand Resonance Measures to Access, Dimensionality, Reliability and Validity

Abstract: The aim of the present study is to analyze brand resonance measures to assess reliability, dimensionality and validity using existing models of brand resonance. This study is based on a mixed approach of research methodology, using qualitative and quantitative methods. In the qualitative approach, we use expert interview and focus group discussion tools. In the quantitative approach, a corporate survey was conducted and 560 responses were collected through a structured questionnaire. The analysis is performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In previous literature review of Keller's (2008) brand resonance pyramid it presents left half belongs to the utility function of brand efficacy and right half affect perception to meet consumers' psychological needs. The combination of utility and emotional functions allows consumers to reach a stage of resonance with the brand (Raut et al, 2020). Therefore, to see a whole frame of brand resonance, future research can examine the utility factors such as brand attributes in price, design, fabric, comfort, color, etc.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous literature review of Keller's (2008) brand resonance pyramid it presents left half belongs to the utility function of brand efficacy and right half affect perception to meet consumers' psychological needs. The combination of utility and emotional functions allows consumers to reach a stage of resonance with the brand (Raut et al, 2020). Therefore, to see a whole frame of brand resonance, future research can examine the utility factors such as brand attributes in price, design, fabric, comfort, color, etc.…”
Section: Research Resultsmentioning
confidence: 99%
“…The right half belongs to the perceptual level where brand image will affect perception to meet the psychological and emotional needs of consumers. The combination of these two levels allows consumers to reach a stage of resonance with the brand (Raut, Brito, & Pawar, 2020). Brand Resonance refers to the characteristics of the relationship between the customer and the brand; and refers to the degree of synchronization between the customer and the brand (Raut et al, 2020).…”
Section: Stayreal Brandmentioning
confidence: 99%
“…The study by Tran et al, (2020);and Raut et al, (2020) suggested that CFA can be used to measure convergent validity through assessment of the factor loadings. The result in Table 8 indicates that factor loadings for brand attitude, brand awareness, brand reputation and brand performance are greater than 0.5.…”
Section: Validity and Reliability Testmentioning
confidence: 99%
“…Results from Factor Analysis: According to Raut et al, (2020) it is necessary to conduct Kaiser-Meyer-Olkin (KMO) test before factor analysis. Lechien, et al, (2020) suggested that Kaiser-Meyer-Olkin (KMO) and Bartlett's Test of sphericity must be tested for purpose of identifying the fitness of the data for factor analysis.…”
Section: Validity and Reliability Testmentioning
confidence: 99%
“…Within the marketing literature, the concept of brand resonance is particularly strong. This refers to the relationship a customer has with a product and the degree to which we, as a customer, believe we are compatible with the brand or believe we and the brand share the same values (Keller, 2012; Raut, Brito, & Pawar, 2020). Brand resonance is highly prized as it means a product has both reached an audience in terms of salience but also that the product has become meaningful to customers.…”
Section: Introductionmentioning
confidence: 99%